The Swinging Woman. Phaedra and Swing in Classical Greece. - Federica Doria; Marco Giuman (Medea, 2016)
In classical myth Phaedra plays a particular role: a main figure in ancient literature (Euripides, Ovid, Seneca write extensively about her vicissitudes), she occupies a very limited space in the artistic repertoire of the classical world. In the Greek world, Phaedra’s figure is unknown to the Hellenic artistic repertoires. There is however an interesting exception: the pictures painted by Polygnotos for the Lesche of the Cnidians at Delphoi, where Phaedra is on a swing. The annotation of Pausania is by no means  secondary: it is common knowledge, as the myths of Erigon or Charila show, that there is a very close symbolic connection between the swing and the hanging, which is also how Phaedra chooses to kill herself. But the binomial swing/hanging, mainly related to sexual relations by ancient sources, also represents symbolically the kind of death enacted in female puberty rituals.